Maintenance of patient-reported health-related quality of life post neoadjuvant relugolix prior to the initiation of prostate radiation therapy - Koh, Min Jung; Koh, Min Ji; Hsueh, Jessica Y.; Gallagher, Lindsey; Danner, Malika; Zwart, Alan; Ayoob, Marilyn; Kumar, Deepak; Carrasquilla, Michael; Leger, Paul; Dawson, Nancy A.; Suy, Simeng; et al. (Frontiers in Oncology, 2025)
IntroductionStudies have demonstrated that injectable GnRH receptor agonists further suppress cancer progression when paired with radiotherapy (RT) in patients with intermediate- to high-risk prostate adenocarcinoma. Relugolix is a newly available oral GnRH receptor antagonist that achieves swift and profound castration (total testosterone <20 ng/dl) at high rates, which may shape patients’ health-related quality of life. The main objective of this prospective study was to explore the effects of neoadjuvant relugolix on health-related quality of life in prostate cancer patients immediately prior to stereotactic body radiation therapy (SBRT).MethodsPatients treated at Georgetown between January 2021 and September 2023 with neoadjuvant relugolix per an institutional protocol were included in the study (IRB 12-1775). The five-item EQ-5D-3L, a well-established tool for quantifying patient-reported health status, was administered to each patient at baseline (prior to relugolix treatment) and again 1 h before the start of SBRT. Higher EQ Visual Analog Scale (VAS) overall scores reflected better quality of life (range 0 to 100). In line with the questionnaire framework, individual elements (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) were rated on a three-point scale from 1 (no problems) to 3 (severe problems). McNemar’s test and paired-sample t-test were performed to analyze changes pre- and post-relugolix treatment. Our investigation determined clinical significance based on minimally important difference (MID) calculated as 0.5 times the baseline standard deviation.ResultsAmong the 87 patients, average age was 71 years, 42% were non-white, and 24% were considered obese (BMI ≥30 kg/m²). Relugolix was initiated a median of 4 months before SBRT initiation (IQR: 3.9–5.4), with 87% of patients reaching profound castration (<20 ng/dl). The VAS overall score was notably higher at baseline (mean ± SD: 82 ± 10) compared to the paired score before RT (79 ± 14, p = 0.02), although this difference was not clinically significant. No statistically or clinically significant changes were observed in any of the five individual items.ConclusionThe use of neoadjuvant relugolix prior to prostate radiation therapy had no clinically significant impact on patient-reported health-related quality of life. Moreover, no statistically significant reductions were observed in any of the five individual health-related quality of life measures. As a key direction for future research, relugolix-associated changes to healthy-related quality of life should be contrasted to those brought about by injectable GnRH agonists.